We still belong - Day, Christine, 1993- (New York, NY : Heartdrum, 2023)
Wesley's hopeful plans for Indigenous Peoples' Day (and asking her crush to the dance) go all wrong-until she finds herself surrounded by the love of her Indigenous family and community at the intertribal powwow.
5.3
5-8
Keywords: Indigenous Peoples' Day -- Juvenile fiction; Indians of North America -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Families -- Juvenile fiction; Indigenous Peoples' Day -- Fiction; Indians of North America -- Fiction; Identity -- Fiction; Interpersonal relations -- Fiction; Family life -- Fiction; Realistic fiction